2008
DOI: 10.1111/j.1365-2311.2008.01009.x
|View full text |Cite
|
Sign up to set email alerts
|

Avoidance responses of an aphidophagous ladybird, Adalia bipunctata, to aphid‐tending ants

Abstract: 1. Insect predators often aggregrate to patches of high prey density and use prey chemicals as cues for oviposition. If prey have mutualistic guardians such as ants, however, then these patches may be less suitable for predators. 2. Ants often tend aphids and defend them against predators such as ladybirds. Here, we show that ants can reduce ladybird performance by destroying eggs and physically attacking larvae and adults. 3. Unless ladybirds are able to defend against ant attacks they are likely to have adap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 43 publications
2
33
0
Order By: Relevance
“…These behavioural patterns may support the findings of other studies that have found negative associations between ants and some carabids (Niemela et al, 1992;Koivula et al, 1999;Reznikova & Dorosheva, 2004;McColl, 2010). Our findings are also in agreement with other studies that have found that some insects are able to perceive and respond to signals o f ant presence (Offenberg et al, 2004;Oliver et al, 2008;Van Mele et al, 2009). …”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…These behavioural patterns may support the findings of other studies that have found negative associations between ants and some carabids (Niemela et al, 1992;Koivula et al, 1999;Reznikova & Dorosheva, 2004;McColl, 2010). Our findings are also in agreement with other studies that have found that some insects are able to perceive and respond to signals o f ant presence (Offenberg et al, 2004;Oliver et al, 2008;Van Mele et al, 2009). …”
Section: Discussionsupporting
confidence: 93%
“…The mechanisms of such effects, however, are not known. Aggressive behaviour, e.g., as shown for the negative effect of Lasius niger L. ants on cocinellid beetles (Adalia bipunctata L.) (Oliver et al, 2008), is one possible mechanism. Some insects may also have the ability to detect the chemical signals associated with ants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, non -myrmecophilous coccinellids frequently leave ant -attended aphid colonies, and may also avoid laying eggs in these patches (Oliver et al 2008 ).…”
Section: Non-myrmecophilous Coccinellid Speciesmentioning
confidence: 99%